2008
DOI: 10.1063/1.2949929
|View full text |Cite
|
Sign up to set email alerts
|

Bifurcational mechanisms of synchronization of a resonant limit cycle on a two-dimensional torus

Abstract: We study synchronization of a resonant limit cycle on a two-dimensional torus with an external harmonic signal. The regime of the resonant limit cycle is realized in a system of two coupled Van der Pol oscillators; we consider the resonances 1:1 and 1:3. We analyze the influence of coupling strength between the oscillators. We show that the resonant limit cycle can be generally synchronized on the torus through the resonance destruction followed by the locking of one and then another one of the basic frequenci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
25
0
4

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 7 publications
(7 reference statements)
5
25
0
4
Order By: Relevance
“…These bifurcations are generated when a stable invariant two-torus and a saddle invariant two-torus merge and disappear. Discussions in the literature [18,19,25] and the results of the present study strongly suggest that a qualitative transition from a stable n-dimensional torus to a stable (n + 1)-dimensional torus is generated by the saddle-node (SN) bifurcations of a stable n-dimensional torus and a saddle n-dimensional torus.…”
Section: Introductionmentioning
confidence: 67%
See 2 more Smart Citations
“…These bifurcations are generated when a stable invariant two-torus and a saddle invariant two-torus merge and disappear. Discussions in the literature [18,19,25] and the results of the present study strongly suggest that a qualitative transition from a stable n-dimensional torus to a stable (n + 1)-dimensional torus is generated by the saddle-node (SN) bifurcations of a stable n-dimensional torus and a saddle n-dimensional torus.…”
Section: Introductionmentioning
confidence: 67%
“…This transition was identified as a QSN bifurcation in continuous-time dynamical systems. Kamiyama et al attempted to fill the gap between the analyses of Broer et al [1] and Anishchenko et al [18,19] by illustrating Arnol'd resonance webs in a coupled delayed logistic map that generates an invariant two-torus [25]. They showed that QSN bifurcations occur when a stable invariant one-torus and a saddle invariant one-torus merge and disappear.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Moreover, Anishchenko et al investigated the geometric structure of a QSN bifurcation [12,13]. They showed that a stable three-dimensional torus occurs because of the saddle-node bifurcation of a stable two-dimensional torus and a saddle twodimensional torus.…”
Section: Introductionmentioning
confidence: 97%
“…The first one is a global coupling, where all-to-all coupling is present, hence the oscillators are connected with each other by direct links or by the mean field [1][2][3][4]. The second type is a local coupling, where the single oscillator is connected to nodes in its nearest neighborhood [5][6][7][8][9][10]. In this work we consider the local coupling.…”
Section: Introductionmentioning
confidence: 99%